Variation in Seed Germination and Seedling Growth of Acacia nilotica ssp. indica Provenances - Krishan, Bal; Toky, O P (Annals of Arid Zone, 2016)
Variation in gemination of scarified and non-scarified seeds, effect of seed coat dormancy on germination and seedling growth of 21 provenances of Babul (Acacia nilotica ssp. indica), collected from 110 to 310N latitude and 19 to 650 m altitude throughout India were studied . There were significant differences among the provenances for germination in non-scarified (16- 92%) and scarified seeds (68-100%). Better seedling growth was observed for scarified seeds. The variation were random and did not show relationship with the latitude of the origin seed source.